2020
DOI: 10.1186/s11556-020-00252-8
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation and validation of the Polish version of the physical activity scale for older people living in a community: a cross-sectional study

Abstract: Background Polish clinicians and researchers face challenges in selecting physical activity tools appropriate and validated for older people. The aim of this study is to provide cultural adaptation and validation of the Polish version of the Physical Activity Scale for Elderly (PASE-P). Methods This cross-sectional study was carried out among 115 older adults living in south-eastern Poland. The original version of the scale has been translated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…60,84 Sixteen studies reported on the test-retest reliability of the PASE, time frames ranging from 3 days 100, 106 to 3-7 weeks 13 and sample sizes ranging from 18 99 to 349 101 (details available in Table 3). Across all versions of the PASE 12 studies reporting ICCs for the total score, only two fell below acceptable limits proposed in the COSMIN guidelines 111 108 . Two studies also included standard errors of measurement for the PASE total score (Chinese version 6.93 63 and NR version 30.00 84 ).…”
Section: Psychometric Properties Of the Pasementioning
confidence: 76%
See 2 more Smart Citations
“…60,84 Sixteen studies reported on the test-retest reliability of the PASE, time frames ranging from 3 days 100, 106 to 3-7 weeks 13 and sample sizes ranging from 18 99 to 349 101 (details available in Table 3). Across all versions of the PASE 12 studies reporting ICCs for the total score, only two fell below acceptable limits proposed in the COSMIN guidelines 111 108 . Two studies also included standard errors of measurement for the PASE total score (Chinese version 6.93 63 and NR version 30.00 84 ).…”
Section: Psychometric Properties Of the Pasementioning
confidence: 76%
“…Several papers evaluated the psychometric properties of the original PASE (n=5) along with a number of validation studies (n=14) for different translations and clinical populations (acute coronary event, 99 COPD 63 , Cancer 22,61 , and Parkinson's disease 84 ). In total, ten different versions of the PASE were assessed for reliability and/or validity in community-dwelling older adults, including: English (n=5), 13,14,61,99,100 Malay (n=2), 101,102 Arabic (n=1), 103 Chinese (n=2), 63,104 Italian (n=1), 105 Norwegian (n=1), 106 Persian (n=1), 107 Polish (n=1), 108 Taiwanese (n=2), 22,109 Turkish (n=1), 110 and two studies did not report the version. 60,84 Sixteen studies reported on the test-retest reliability of the PASE, time frames ranging from 3 days 100, 106 to 3-7 weeks 13 and sample sizes ranging from 18 99 to 349 101 (details available in Table 3).…”
Section: Psychometric Properties Of the Pasementioning
confidence: 99%
See 1 more Smart Citation
“…The maximum number of points on this scale is 24, indicating proficiency in the performance of complex activities of daily living [ 19 ]. The IADL scale was validated in Polish [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results are presented in the form of three ranges: full function (5–6 points), moderate impairment (3–4 points), and complete impairment (1–2 points) [ 20 ]. The Katz ADL scale was validated in Polish [ 15 ].…”
Section: Methodsmentioning
confidence: 99%